Effect of Eucalyptus camaldulensis Terpens, Alkaloids and Phenols Agnaist Fusarium oxysporum - J. Fradi, Ahmed; Al-Araji, Alaa M.Y. (Iraqi Journal of Science, 2023)
This study includes isolation, purification, and identification of Fusarium oxysporum from chili pepper infected plants. Eucalyptus camaldulensis were collected and air dried at room temperature, then ground to semi powdered state. Phenols, alkaloids and terpens were extracted from Eucalyptus camaldulensis. The antifungal activity, type of extracts was evaluated at different concentrations 5 and 10 mg / ml of these compounds were prepared and their antagonistic activity was studied. The Percentage of radial growth inhibition of fungi by plant extracts was measured after 7 day incubation. Results showed that terpens extract was the most active against fungi and alkaloids extract had less antifungal activity and the percentage of mycelia radial growth were 99.55 % – 72.44 % respectively.